Assessment of onion production practices and effects of N:P2O5:S fertilizers rates on yield and yield components of onion (Allium cepa l.) under irrigated farming system in Dembiya District, Amhara Region, Ethiopia - Nigatu, M. (Bahir Dar University, 2016)
The study was initiated with assessing onion production practices and effects of N: P2O5:S, fertilizer rates on yield of Onion (Allium Cepa L.) under irrigated farming system in Dembyia, District, Amhara Region, Ethiopia. The work has two components namely assessing onion production practices in Sufankara, Guramba and Debir zuria kebeles and evaluating the effects of N: P2O5:S, fertilizer rates on yield and yield components of onion in Jenda kebele. The study was conducted during 2014/15 under irrigation. To assess onion production practices data was collected from 30 onion producing households using semi-structured questioners, focus group discussions, data on demographic structure and the whole value chain of onion production system were recorded and analyzed using SPSS version 20. In the experimental part twelve different N: P2O5:S fertilizer rates were tested. The experiment was laid down in randomized complete block design (RCBD) with three replications. Data on vegetative and yield parameters were collected and analyzed using SAS version 9.0 computer soft ware. The survey result indicated that most of the onion producers in the study area did not implemented the recommended irrigation cultural practices of onion, Limited supply of improved onion seeds also one of the important factor that contributes to low productivities of onion in the study area. Low rates of fertilizers application, low population of onion plants per unit area, high incidence of disease and insect pests, shortage of pesticides and their adulteration characterize the onion production system under farmer’s practice. As a result the productivity of onion under farmers was low (85.6q/ha) compared with the national production (101q/ha). Besides the average crop water productivity was (1.74 kg/m3) which were relatively low with compared to other researches on onion crop water productivity (4.62 kg/m3)). Although the quantity of water is similar with the requirement of onion (4,914 m3/ha), but the yield obtained is low. The major constraints of onion production in the study area were shortage of irrigation water, high costs of irrigation equipments, shortage of genuine spare parts and accessories, shortage of pesticides and their adulteration, limited supply of improved onion seeds and lack of storage facilities, lack of skills and knowledge, high incidence of diseases and insect pests and weak extension and credit services. Results of N: P2O5:S, rate trial revealed that most of growth and yield parameters of onion were significantly influenced by N: P2O5:S fertilizer rates. The highest plant height (60.1 cm), leaf length (50.1cm) and maturity days (142 days) were recorded in 73.5:92:16.95, 136.5:119.6:22 and 136.5:119.6:22 kg ha-1 N: P2O5: S, application rates respectively. The highest bulb weight (198.8g), marketable yield (20.8t/ha), non marketable yields (0.509 t/ha) and total bulb yield (21.398t/ha) were recorded offer 105:119.6:22 kg ha-1 N:P2O5:S application rate . Onion plants without N: P2O5:S, fertilizer applications were inferior in all growth and yield parameters. For enhancement of production and productivity of onion in Dembyia district and other similar environment, it is necessary to solve problems indicated above through training, extension activities and improving the supply of inputs. Application of N: P2O5:S fertilizer at the rate of 105:119.6:22 N:P2O5:S kg ha-1 was economically feasible and thus can be recommended for the production of onion in the study area. However is advised to repeat the experiment to have forceful recommendation